Factorial structure of the Buss-Perry Aggression Questionnaire (BPQA) in Polish population - Aranowska, Elżbieta; Rytel, Jolanta (Studia Psychologica: Theoria et praxis, 2012)
Aggression can be evaluated in a variety of ways. Among the self-reported measures, the Buss-Durkee Hostility Inventory (Buss, Durkee, 1957) has been one of the most popular questionnaire. On the basis of this previous work, Buss and Perry proposed a psychometrically improved and updated measure of aggression: The Aggression Questionnaire (Buss, Perry, 1992). The Buss-Perry Aggression Questionnaire (BPQA) has quickly become the gold-standard for the measurement of aggression. The original version of the BPAQ contains 29 items and is designed to assess four dispositional components of aggression: Physical Aggression, Verbal Aggression, Anger, and Hostility. However, the BPAQ scale has been extensively validated, the validation focused, mainly, on samples of college students. In this study, exploratory and confirmatory models were evaluated among a sample of 3990 Polish participants (aged from 10 to 79 years). A 5-factor structure resulted in the exploratory analysis and 5-factor structure showed acceptable fits in confirmatory analyses. Implications and limitations of these solutions are discussed.